Primates of Peninsular Malaysia - Mohd Ridwan, Abd Rahman (Jabatan Perlindungan Hidupan Liar dan Taman Negara (PERHILITAN) Semenanjung Malaysia, 2022)
Malaysia has highly diverse primates with 25 species currently. However, not all of us are familiar the primate species that is present in this country. This book aims to highlight the diversity of primates in Malaysia, and focusing on primates found in Peninsular Malaysia. This book is the first to feature a compilation of primate photos in Peninsular Malaysia produced by Malaysians. This book can be used as a primary reference in identification of primates more accurately based on featured photos. It is hoped that this book will benefit all including the Ministry of Energy and Natural Resources (KeTSA), PERHILITAN, Forestry Department Peninsular Malaysia, zoological parks, other stakeholders and the general public.